Opioid Analgesics Suppress Male Gonadal Function, but Opioid Use in Men and Women Does Not Correlate with Symptoms of Sexual Dysfunction - Dana Wong; Dan Gray; Mark Simmonds; Saifee Rashiq; Igor Sobolev; Donald W Morrish (Pain Research and Management)
BACKGROUND: Opioid analgesia impairs gonadal function in men and women, but the correlation with symptoms and hormonal measurements of hypogonadism is not well established.